Do adult men with untreated ventral penile curvature have adverse outcomes?. Issue 1 (February 2016) - Menon, Vani; Breyer, Benjamin; Copp, Hillary L.; Baskin, Laurence; Disandro, Michael; Schlomer, Bruce J.
Summary: Introduction: Congenital ventral penile curvature without hypospadias is often treated surgically in childhood. The history of untreated ventral curvature is unknown. Objective: This study's aim was to examine the association of untreated ventral penile curvature with various sexual and psychosexual outcomes. Study design: An electronic survey was advertised to men older than 18 years on Facebook. Men with possible ventral penile curvature identified themselves by choosing sketches that most closely represented their anatomy. Outcomes assessed included: Sexual Health Inventory for Men, difficulty of intercourse because of curvature, International Prostate Symptom Score, Penile Perception Score, psychosexual milestones, paternity, infertility, sitting to urinate, and the CDC HRQOL-4 module. Results: Among participants, 81 out of 684 men (11.8%) reported untreated ventral penile curvature. Participants with self-reported curvature noted more difficulty with intercourse because of curvature (4.5 vs 4.9, p  < 0.001), more unhealthy mental days (8.6 vs 6.2, p  = 0.02), and increased dissatisfaction with penile self-perception compared with men without reported curvature (8.6 vs 9.5, p  < 0.001). Discussion: Men with possible untreated ventral curvature reported worse penile perception scores, more mentally unhealthy days, and increased difficulty with intercourse secondary to curvature compared with men without curvature. A limitation to this study is selection bias; responses collected were self-reported from survey volunteers. Additionally, the question identifying ventral penile curvature is not validated but performed well in pretesting. Most questions were from validated surveys, but some were modeled after validated surveys and/or contained high face validity types of questions. Conclusion: Men with possible untreated ventral penile curvature reported more dissatisfaction with penile appearance, increased difficulty with intercourse, and more unhealthy mental days. Given high success rates, low complications, and improved outcomes after surgical correction of penile curvature reported in the literature, our results support correction of congenital penile curvature in childhood.